KINERJA KELEMBAGAAN INPUT PRODUKSI DALAM AGRIBISNIS PADI DI KABUPATEN PARIGI MOUTONG - Sisfahyuni Sisfahyuni (Agroland: Jurnal Ilmu-ilmu Pertanian, 2008)
The aim of the study was to identify the performance of the loan service of the Bank Rakyat Indonesia, seed institution (seed agency and PT. Pertani), and producer and fertilizer distributor (PT. Pusri) in supporting the rice agribusiness input subsystem. The data were analyzed using cross tabulation and performance evaluation based on input, output, outcomes and benefit indicators.The results of the study indicated that the performance of the Bank Rakyat Indonesia, PT. Pertani, and seed agency was categorized as low.  This means that these institutions cannot support the rice agribusiness input subsystem.  Whereas the performance of PT. Pusri was categorized as high, meaning that this institution has succeeded in supporting the rice agribusiness input subsystem in Parigi Moutong district.